Modelne raziskave razogljičenja talin - Godicelj, Tomaž (Kovine zlitine tehnologije, 1995)
Most of steel is made from pig iron which has high carbon content. The intention of the project was to find how model investigations can help in studying the decarbuzation processes. In the reactor model the decarbuzation reaction was simulated by using 0.1 M KOH solution and blowing of CO sup 2 and N sup 2. Such model investigation enable the understanding of the effects of the gas being blown on and through the melt, on the formation of interfase surfaces. The investigations consisted of two stages. In the first stage, gas mixture was introduced through three tuyeres, being placed in the reactor bottom in a row which did not coincide with the central line. The influence of the number of tuyeres and their arraying, and on the height/diameter ratio of the bath on the flow patternes was studied. In the second stage, the decarburization process with the lance mouth from the melt surface, a constant amount of CO sup 2 + N sup 2 gas mixure was introducted, while N sup 2 for melt stirring was blown through eight nozzles in three different concentric circles on the reactor bottom. Measurement of electrical conductivity enabled the determination of variations of initial concentrations. The described results show the possibility for model investigations of the processes, enabling its optimization towards a reduced duration of the process and an increased throughput of the reactor.
Keywords: Metallurgical and Materials Engineering; metalurgija; zlitine; talina; modelne raziskave; razogljičenje